Guerres et violences à l’abbaye d’Ardenne - Yves Chevrefils Desbiolles (Revue LISA)
Ardenne Abbey (on the outskirts of Caen, Basse-Normandie, France) is nowadays the headquarters of the Institut Mémoires de l’Édition Contemporaine, which houses archives dedicated to the intellectual life of the twentieth century. The mission of the IMEC is well suited to such a place: the images associated with the word “abbey” revolve around the idea of Peace through study, prayer or choral singing. This idyllic vision of an abbey, however, is in no way a protection against the vicissitudes of history. Perhaps even the contrary. An abbey, through what it represents, often becomes a symbolic target that makes it the victim of all sorts of violence. Before focusing on the Second World War, which almost led to its final disappearance, this article discusses the history of Ardenne Abbey from the Middle Ages to the modern era, in the light of the dark topic of violence.